HUKUM SALAT BERJEMAAH DI MASJID DENGAN SAF TERPISAH KARENA WABAH - Eko Misbahuddin Hasibuan; Muhammad Yusram (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This article aimed to describe the law of congregational prayer in mosque with tenuous line due to Corona outbreak that hits this country. This study used a descriptive qualitative approach that describes Islamic concepts that need to be understood and implemented in the matter of congregational prayer in unusual situation by analyzing the propositions and opinions of the scholars. The results of this study indicate that if there were instruction to temporarily discontinue Friday prayers and congregational prayers in the mosque that is merely an appeal and an institution or mosque takmir decided to continue conducting congregational prayers in the mosque by applying social distancing, then their congregational prayers would be considered legal. However, obeying the appeal of the authorities, both the government and Indonesian Council of Ulama (MUI), is more recommended and preferred. It is because an appeal, although not compulsory, is intended to benefit the community in general, and the appeal is issued owing to the danger of Corona outbreak that is obvious and real. This appeal is enough to be considered excuse for discontinuing the congregational prayers in the mosque and substituting Friday prayer with four-rakat Zuhr prayer.